Perancangan Sistem Informasi Administrasi Pembayaran Spp Pada Smk Batanghari Kota Jambi - Sujatmiko, Tri Aji; Maulana Hidayat; Pajri; Abidin, Dodo Zaenal (LPPM Universitas Dinamika Bangsa, 2024)
ABSTRACT Tri Aji Sujatmiko 8020180256, Maulana Hidayat 8020190016, Pajri 8020190025 DESIGN OF A WEB-BASED SPP ADMINISTRATION PAYMENT INFORMATION SYSTEM AT SMK BATANGHARI JAMBI CITY Keywords: Design, System, Information, Payment, Tuition Payment, Website. In today's digital era, efficiency and effectiveness in school administration will definitely be important. One important aspect of school administration is the payment of SPP (Education Development Contribution). SMK Batanghari Jambi City needs a system that can simplify the SPP payment process, reduce data entry errors, and increase transparency. In this research, we will design and develop a web-based tuition payment information system that can be accessed by students, parents, and schools. With a software development method that involves requirements analysis, system design, implementation, and testing. The result of the design is a website that allows users to pay tuition fees online, storage of payment history, and real time financial reports. This system is expected to improve the efficiency of managing tuition payments at SMK Batanghari Jambi City and provide easy access to information to all interested parties.